Step by action solution :

Step 1 :

Equation at the finish of action 1 : 3x2 - x = 0

Step 2 :

Step 3 :

Pulling out like terms :3.1 traction out favor factors:3x2 - x=x•(3x - 1)

Equation at the finish of action 3 :

x • (3x - 1) = 0

Step 4 :

Theory - root of a product :4.1 A product of numerous terms amounts to zero.When a product of two or more terms equals zero, then at the very least one that the terms have to be zero.We shall currently solve each term = 0 separatelyIn various other words, we are going to deal with as many equations as there are terms in the productAny systems of hatchet = 0 solves product = 0 as well.

Solving a solitary Variable Equation:4.2Solve:x = 0 systems is x = 0

Solving a solitary Variable Equation:4.3Solve:3x-1 = 0Add 1 come both sides of the equation:3x = 1 divide both sides of the equation by 3:x = 1/3 = 0.333

Two services were found :

x = 1/3 = 0.333x = 0




You are watching: How to factor 3x^2-x-2

Why discover this

*

Terms and topics

*

Related links

*

abc
a
x
y
/
|abs|
( )
7
8
9
*
4
5
6
-
%
1
2
3
+
0
,
.
=
abc
a
b
c
d
e
f
g
h
i
j
k
l
m
n
o
p
q
r
s
t
u
v
w
x
y
z

.
*



See more: What Is The Lcm Of 3 And 13 And 39), Least Common Multiple (Lcm) Of 3, 13, And 33

ago to peak